Effect of highly active antiretroviral therapy on the natural history of anal squamous intraepithelial lesions and anal human papillomavirus infection - Palefsky, J M; Holly, E A; Ralston, M L; Da Costa, M; Bonner, H; Jay, N; Berry, J M; Darragh, T M (Journal of acquired immune deficiency syndromes (1999), 2001)
The effect of highly active antiretroviral therapy (HAART) on the natural history of anal squamous intraepithelial lesions (ASIL)-the likely anal cancer precursor-and anal human papillomavirus (HPV) infection is unknown. ASIL severity and level of anal HPV DNA were evaluated among HIV-positive men who have sex with men (MSM) for at least 6 months before initiation of HAART. The results were compared with those from a 6-month period after initiation of HAART. Anal swabs for cytology and HPV studies were obtained, followed by high-resolution anoscopy and biopsy. Among men whose most severe pre-HAART diagnosis was atypical squamous cells of undetermined significance or low-grade ASIL, 18% (confidence interval [CI], 6-31%, 7 of 38) progressed and 21% (CI, 8-34%, 8 of 38) regressed 6 months after starting HAART. Seventeen percent (CI, 0-38%, 2 of 12) of study subjects who began with a normal diagnosis developed ASIL. Only 4% (CI, 0-10%, 1 of 28) of study subjects with high-grade ASIL regressed to normal. There was no reduction in the proportion of study subjects who tested positive for HPV DNA or HPV DNA levels after HAART initiation. The ASIL and HPV data were similar to those of the pre-HAART comparison period. These results indicate that HAART has little effect on either ASIL or HPV in the first 6 months after HAART initiation.